Air travel is associated with intracontinental spread of dengue virus serotypes 1-3 in Brazil. - Marcio R T Nunes; Gustavo Palacios; Nuno Rodrigues Faria; Edivaldo Costa Sousa; Jamilla A Pantoja; Sueli G Rodrigues; Valéria L Carvalho; Daniele B A Medeiros; Nazir Savji; Guy Baele; Marc A Suchard; Philippe Lemey; et al. (Public Library of Science (PLoS), 2014)
Dengue virus and its four serotypes (DENV-1 to DENV-4) infect 390 million people and are implicated in at least 25,000 deaths annually, with the largest disease burden in tropical and subtropical regions. We investigated the spatial dynamics of DENV-1, DENV-2 and DENV-3 in Brazil by applying a statistical framework to complete genome sequences. For all three serotypes, we estimated that the introduction of new lineages occurred within 7 to 10-year intervals. New lineages were most likely to be imported from the Caribbean region to the North and Northeast regions of Brazil, and then to disperse at a rate of approximately 0.5 km/day. Joint statistical analysis of evolutionary, epidemiological and ecological data indicates that aerial transportation of humans and/or vector mosquitoes, rather than Aedes aegypti infestation rates or geographical distances, determine dengue virus spread in Brazil.